Zeros of orthogonal polynomials generated by canonical perturbations of measures - Huertas, Edmundo J.; Marcellan, Francisco; Rafaeli, Fernando R. [UNESP] (Elsevier B.V., 2012)
In this paper we analyze the behaviour of the zeros of polynomials orthogonal with respect to the Uvarov perturbation of a positive Borel measure d mu(x). When the measure is semi-classical, then its electrostatic interpretation is given. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: Orthogonal polynomials; Interlacing; Monotonicity; Asymptotic behavior; Electrostatics interpretation